ASITA 2009: tra sviluppo sostenibile e conoscenza del territorio - Redazione, Redazione (GEOmedia, 2009)
ASITA 2009: sustainable development meets land knowledge ASITA 13th edition was held in Bari, in the Puglia region, since 1st until the 4th of december 2009. Main focus of the event, which featured almost 400 papers, 4 special sessions and 21 ordinary sessions, was sustainable development in all its aspects. A correct government policy dedicated to the land and the environment is necessary in order to face future challenges. De-standardisation and lack of central organisation are the main problems that the italian decision makers must consider before starting any common land policy.